2020
DOI: 10.7717/peerj.8394
|View full text |Cite
|
Sign up to set email alerts
|

LINC00844 promotes proliferation and migration of hepatocellular carcinoma by regulating NDRG1 expression

Abstract: Background Aberrant expression of long noncoding RNAs are implicated in the pathogenesis of human malignancies. LINC00844 expression is dramatically downregulated in prostate cancer, and functional studies have revealed the association between the aberrant expression of LINC00844 and prostate cancer cell invasion and metastasis. However, the function and mechanism of action of LINC00844 in the pathogenesis of hepatocellular carcinoma (HCC) are poorly understood. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 33 publications
0
6
1
Order By: Relevance
“…Notably, an existing study also acknowledged the profound inhibitory effects of LINC00844 in malignant and metastatic PC by preventing migration and invasion (Lingadahalli et al, 2018), which further confirmed our findings to classify LINC00844 as a tumor suppressor. Although in the prior study, the authors claimed that LINC00844 did not extensively affect PC cell proliferation, our findings suggested that (Zhou et al, 2020). Therefore, it can be ascertained that LINC00844 exercises a repressing effect on PC progression based on the aforementioned findings.…”
Section: Discussioncontrasting
confidence: 48%
“…Notably, an existing study also acknowledged the profound inhibitory effects of LINC00844 in malignant and metastatic PC by preventing migration and invasion (Lingadahalli et al, 2018), which further confirmed our findings to classify LINC00844 as a tumor suppressor. Although in the prior study, the authors claimed that LINC00844 did not extensively affect PC cell proliferation, our findings suggested that (Zhou et al, 2020). Therefore, it can be ascertained that LINC00844 exercises a repressing effect on PC progression based on the aforementioned findings.…”
Section: Discussioncontrasting
confidence: 48%
“…In the signature, we identified six LncRNAs (FOXD2-AS1, AC062021.1, AF131216.5, LINC00844, CRNDE and LINC00665). FOXD2-AS1 (32, 33), LINC00844 (34,35), CRNDE (5,6), and LINC00665 (36,37) were reported to have the similar biological functions and to be associated with prognosis, cell proliferation, invasion, cell cycle, and metastasis. Meanwhile, as demonstrated by existing reports, glycolysis activity has implicated in the cell proliferation (9-11), cytotoxic activity (38), immune response (39,40), drug resistance (41,42), poor prognosis (43)(44)(45)(46), and tumor microenvironment (47) in most cancers.…”
Section: Discussionmentioning
confidence: 99%
“…We observed that most of these ncRNAs (37/39) were downregulated in the aggressive subtype CC2, implying their tumour‐suppressive functions (Figure 2A). Indeed, LINC00844 , the lowest‐ranked ncRNA in CC2, has been reported to have a tumour‐suppressive function in HCC and other cancer types 13,14 . By contrast, HAGLR ( HOXD‐AS1 ), the top‐ranked ncRNA in CC2, has been reported to promote HCC metastasis 15 .…”
Section: Resultsmentioning
confidence: 99%